ANALISIS PENGARUH KEPEMIMPINAN,KOMPENSASI DAN STRES KERJA TERHADAP KINERJA PEGAWAI DI DINAS SOSIAL SEMARANG - Indah Rustrinawati, 08.05.51.0037; Darmi Astuti, Sih (Students Journal of Economic and Management, 2012)
The study aims to examine and analyze the effect of leadership, compensation and job stress on employee performance Semarang City Social Services The population in this study were employees of Social Services Semarang, amounting to 435 Slovin calculation formula samples in this study amounted to 81 respondents. The sample in this amount eligible to be therespondent Data analysis techniques in this study using multiple linear regression while hypothesis testing using t-test and F Based on the survey results revealed that there is apositive and significant relationship between leadership (X1) on the performance (Y), whereas no positive and significant relationship between compensation (X2) on the performance of an employee (Y), there is a positive and significant relationship between work stress (X3 ) on the performance of an employee (Y). Keywords: Leadership, Compensation, Work Stress, Performan